Analisis Kemampuan Berpikir Kritis Berdasarkan Gender Kelas Xi Mia Sma Negeri 1 Maiwa Melalui Model Pembelajaran Inkuiri (Studi Pada Materi Pokok Kesetimbangan Kimia) - Imran Hante; Sulfikar Sulfikar; Jusniar Jusniar (ChemEdu, 2020)
This study aims to describe and compare critical thinking skills of students based on gender in class XI MIA of SMA Negeri 1 Maiwa. This comparational descriptive study aims to describe and compare critical thinking skills of students based on gender in class XI MIA of SMA Negeri 1 Maiwa were both classes were taught by using inquiry learning model. The instrument used in this study was observation sheet to measure the process of critical thinking skills and measure the product of critical thinking ability from achievement test. The achievement indicators of critical thinking skills in male and female classes by comparison indicators in giving a simple explanation achieved 41% and 46.3%, building up basic skills achieved 51% and 34.83%, organizing the strategy and tactics is achieved 52% and 25.89%, giving further explanation achieved 44% and 55.3%, and concluding achieved 60% and 58.92%. Achievement test values of critical thinking were analyzed using t-test of both classes where tcalculate < ttable, concluded that there was no difference in critical thinking skills of male and female students in class XI MIA SMA Negeri 1 Maiwa through inquiry learning model in the chemical equilibrium subject.